2018
DOI: 10.1007/s12671-018-0988-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Mindfulness in the General Population

Abstract: Previous research among experienced meditators suggests that the associations of trait mindfulness with mental health are mediated by emotion regulation, body awareness, and a less static perspective of the self. The present study sought to elucidate whether this mediational model is also applicable to the general population and whether further potential mechanisms of action need to be included. Meditators and nonmeditators differ in overall mindfulness levels, but also in the structural properties of mindfuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 51 publications
9
52
1
Order By: Relevance
“…Thus, the instrument bears a strong connection to one theoretical model of mindfulness. Also, psychometric studies have replicably shown that the higher-order structure of the FFMQ agrees well with the two-component model of mindfulness that was proposed by Bishop et al (2004), both in meditating (Tran et al 2014) and nonmeditating samples (Burzler et al 2019;Tran et al 2013). Being both comprehensive and compatible with theoretical models of mindfulness, the FFMQ appears thus to be a viable starting point for deeper analyses of self-reported mindfulness.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…Thus, the instrument bears a strong connection to one theoretical model of mindfulness. Also, psychometric studies have replicably shown that the higher-order structure of the FFMQ agrees well with the two-component model of mindfulness that was proposed by Bishop et al (2004), both in meditating (Tran et al 2014) and nonmeditating samples (Burzler et al 2019;Tran et al 2013). Being both comprehensive and compatible with theoretical models of mindfulness, the FFMQ appears thus to be a viable starting point for deeper analyses of self-reported mindfulness.…”
supporting
confidence: 61%
“…It appears that nonattachment is neither fully distinct from the FFMQ facets (as it loaded on the same factors), nor a unitary mechanism/faculty of mindfulness on its own (as it loaded on multiple factors). However, the current study was based on the full NAS, rather than the abridged NAS-7 (see Sahdra et al 2016), to retain comparability with some previous studies, which also have used the full NAS (e.g., Burzler et al 2019;Tran et al 2014). Clearly, nonattachment deserves further investigation in the future.…”
Section: Nonattachmentmentioning
confidence: 95%
See 3 more Smart Citations